Pengolahan Singkong Karet Menjadi Tepung Mocaf Di Sukabangun Kecamatan Sukarame Kota Palembang - Muhammad Yerizam; Ahmad Husaini; Ellina Margaretty; Aliyah Montessa (Aptekmas Jurnal Pengabdian pada Masyarakat, 2019)
Sukabangun is one of the Sukarami sub-districts in the city of Palembang, South Sumatra, which can be reached approximately 20 minutes from the Sriwijaya State Polytechnic.The targets and outcomes expected from this dedication are the emergence of awareness to utilize Manihot Glaviozii which is rarely used by the society for daily needs, increase business opportunities and create workforce for the local and surrounding society which are still unemployed and teenagers who are no longer attending school and make a mocaf flour as an alternative to wheat flour.The implementation methods of this dedication that is applied includes Presentations and interactive discussions conducted for the targets, namely the residents of Sukarame sub-district, presentation material namely knowledge of processing mocaf flour from Manihot Glaviozii, displaying and giving banners for example mocaf flour, showing a mocaf flour has been processed, digging up the absorption of participants in interactive discussions through question and answer. From the result of this dedication is the residents get the knowledge about the processing of Manihot Glaviozii becomes mocaf flour as an alternative wheat flour so that, it will impact for the economic society in Sukabangun, Sukarame sub-district, Palembang city.